Establish a potential obscure inventory with practical application - Abdulmaneem khadim Hammadi; Rasha Adel Abdel (Journal of Madenat Alelem University College, 2017)
Contain This paper a continuous review study of inventories to establish a model for potential obscure inventory of cement material for Kirkuk plant, The data will used for year (2015) on a quarterly basis in the shed of random demand, which it was build up after specimen test and determine the demand distribution during the supply period (the waiting period), then we test the data after removing obscure and found that they are distributed as (Normal Distribution) the research aims to determine the optimum economic amount of the expected production and the expected total cost and determine the expected shortage level and reorder point, Been proved that the importance of of obscure grouping theory application and their efficiency in reducing environmental effects faced by the company by controlling on demand levels and holding inventory cost, after conducting the required mathematical and statistical analyzes of the data by writing algorithm of proposed and It was using special mathematical criteria of quantitative methods in addition to the application importance and inventory effectiveness of the potential model in determining the economic quantities of production when the demand is random and obscure and reduced investment in inventories which leading to lower total costs of inventory to a minimum and so as to give solutions for research problem